Accounting students’ perspective of learning law course - Ambaras Khan, Hanna (Asia Pacific Academy of Science, 2022)
Law subject is not exclusive to law students only. There are many faculties that offer law subjects to the students. In terms of teaching and learning law, there are a few methods such as lectures, drafting, and case study. However, teaching law to non-law students needs creativity. The non-law student’s perception of law subject is important to develop interest in the learning process. Most non-law students thought law was difficult and uninteresting. Hence, there is a need to revise the method of teaching and learning to attract students’ attention and interest and to change their perception of learning law subjects. The objective of this research is to study the change in the accounting students as non-law students’ perspective in learning law using a mix of conventional and revised methods, and whether there is any change in their perception. This paper adopts a qualitative research method to collect data. The findings of the research show that a mix of conventional traditional, and revised methods changed students’ perspectives about learning law subjects. The mixed method is seen as fun and suitable for accounting students to learn law. It is suggested to have many other activities created as assessment methods in teaching law to accounting students.